A Possible Mid-Fourth-Century Altar Platform at Marcham/Frilford, Oxfordshire. (14th July 2015) - Warry, Peter
Abstract Marcham/Frilford is a large religious site with a temple, an amphitheatre and a central shrine feature. Adjacent to the shrine is a large fourth-century structure containing a significant deposit of coins, hobnails and bones. The absence of diffusion of the tiles from the temple roof to the wider site suggests that it continued to function as a religious complex throughout the Roman period; therefore the large structure is unlikely to have been a building which would have blighted the shrine but was more probably an altar platform where rituals were performed in conjunction with it.